State and prospects of Serbian SME development - Krstić Milan; Skorup Ana; Obradović Ivan (Trendovi u Poslovanju)
Small and medium-sized enterprises (SMEs) represent a significant economic, segment of the national economy, primarily because of its entrepreneurial activity, but also because of its contribution to the raising of the overall level of competitiveness of the national economy, which has a positive impact on all fields of social life. In order to point out the importance of the development of the SME sector, this paper presents the results of the state and prospects of development of the SME sector in the Republic of Serbia. The basic premise of the research is that the SME sector is a particularly important factor in the economic development of Serbian economy, having a significant potential for further growth and development. In order to confirm the above assumptions, the research focuses on a consideration of the context of the economic space in Serbia in which growth and development of the SME sector occurs, within which analyses of key economic indicators of the Serbian economy were conducted, altogether with the competitiveness of Serbian economy, as web as of the current state of development of the SME sector in Serbia and the perspectives for the future development of SMEs in Serbia. Based on these analyses, the relevant facts are indicated in relation to the current development the SME sector, as well as to the facts that of determine its further development. There from, trends of the future development of the SME sector are forecasted, as web as the potential ways of future treatment of SME sector.